Rancang Bangun Sistem Informasi Akademik Sekolah Menengah Kejuruan Negeri 1 Loea - Irwan Syahib, Muhammad (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
This research aims to develop a web-based academic information system for SMK Negeri 1 Loea, utilizing the waterfall system development methodology. The advancement of information technology is an undeniable aspect of this digital era. One of the widely utilized technological developments is web-based information systems. Currently, many schools have yet to harness the potential of this information system technology to assist students in accessing their academic information. Academic Information Systems have become crucial in the current digital age, especially in remote areas. The result of this research is the successful creation of a web-based academic information system, which has been tested for its functionality and proven to provide ease in data management and information dissemination to students, teachers, and users. By using this system, issues that occasionally arise can be minimized.